LITERARY WRITING: CHALLENGES AND POSSIBILITIES - Oliveira, Andreia dos Santos; Guizelim Similes Girotto, Cyntia Graziella [UNESP]; Pacifico, Juracy Machado (Univ Estadual Sudoeste Bahia, 2019)
Thisproject Literarywriting: challengesandpossibilities wasdevelopedbyhigh school students from integrated course of Institute Federal de Rondonia. Actions started from this problematization: How can students' interests be aroused and motivate them to write texts so different from those that are habitual to the chosen area? For this, it outlined as goal criate environment favorable to reading and writing. To condute this actions, we use the postulates from Fiorin and Savioli (2006) because they defend literary writing as possibility of recreation of world, from Antunes (2003) who introduced us the various phases interdependent and intercomplementary involved in the elaboration of the literary text, and in historical theory cultural from Vygotski (1995) who defend the use of the writing from a need of the subject. As axes of action, we elaborated situations who the high school student had contact with the reading of the literary texts, as they were critical of the process of writing textual, after this, they planned the book, they revised and rewrote. As a result, it has been found that high school students have ceased to be passive readers and writers and became subjects of the action when they saw function in the act of writing.
Keywords: Education; Historical-cultural theory; Literarywriting